To Analyze Patients with Psoriasis’s Dietary Intake and Disease Severity - Thorat, Mayuri Tatyasaheb (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Psoriasis, the most common chronic inflammatory skin condition, affects 0.5 to 4% of people worldwide, depending on the area. It’s common knowledge that having both metabolic syndrome and psoriasis increases the likelihood of the other condition. It has been found that psoriasis shares a polygenic genesis with the autoimmune, inflammatory, and proliferative diseases of the epidermis. Psoriasis is one kind of inflammatory disease that is immune-mediated. This preview does not cover the full potential of gene polymorphism, nor does it discuss the crucial role that epigenetics plays in nutritional biology. Material and Method: The current cross-sectional, observational, and analytical investigation was conducted in the Department of Dermatology. Two hundred male and female psoriasis patients who attended a dermatology clinic were included in the study. The values of the daily dietary nutrient intake—also referred to as exposure variables—are the independent variables. Among them are a number of macro and micronutrients. The dependent variable is the clinical categories determined by disease severity scores. Results: The trial included 200 psoriasis patients in total. A comparison of the measured parameters was done using three clinical classifications of patients with different disease severity: mild, moderate, and severe. The median of the observed daily calorie consumption was 82.16% of the recommended daily food intake amount. Overall, it was demonstrated that low-calorie intakes were more common and progressive as the disease severity rose. Conclusion: The majority of the investigation’s findings are consistent with data from clinical, laboratory, and epidemiological studies. In view of advances in pathogenic understanding, the synthesis of nutrient intake data is an attempt to establish critical aspects for the necessary follow-up work toward the development of specific dietetic recommendations in psoriasis. Focused investigations on large-scale epidemiological and clinical perspectives—which are anticipated from the current study—are required to create specific dietary recommendations for psoriasis. Keywords: Psoriasis, Micronutrients and Omega-3 Polyunsaturated Fatty Acids